Z historii Święta Palanta w Grabowie - Chlebowska, Barbara (Zeszyty Wiejskie, 2014)
The present article is a case study of the Palant Day, organized on Grabów – a small village, with less than 100 inhabitants, situated in the north-western part of the Łódzkie voivodeship. The history of Grabów dates back to the Middle Ages. Until World War II, the settlement was a centre of crafts. It can be assumed that the tradition of palant [a Polish game similar to baseball] was initiated in this place in the early 19th century by the village owner, Feliks Kretkowski. Every year, on the first Tuesday after Easter, a one-of-a-kind Palant Day is organised on Grabów. Local inhabitants sometimes call it “the third day of Easter”. Unfortunately, it is impossible to determine when the habit of playing games on this particular day started. Originally, the Palant Day was a festival of artisans, now it is a celebration organised by the Commune Culture Centre and the Commune Office in Grabów. Today, each resident of the village can be a member of the informal Palant Club and take part in games. The Palant Day is accompanied by artistic performances, e.g. concerts of a wind band and a show of majorettes. It has become an important event for presentation of local amateur artists, and therefore it is an impulse for development of this kind of activity. Due to its exceptional character, the festival attracts the local and national media, so it is an important tool for promotion of the commune. The residents of Grabów have various attitudes to the Palant Day, ranging from pride of the local tradition to indifference which is usually related to the inability to participate in it. The popularity of palant in Grabów is not going to decrease, as the commune has a local school league of palant, and recently a youth palant team has been established.